Strategi Pembelajaran Kombinasi Daring dan Luring Selama Masa Pandemi Covid-19 Pada Kelompok B di TK Sekolah Alam Insan Mulia Surabaya - Indri Widya Ningsih; Ruqoyyah fitri (JIEEC (Journal of Islamic Education for Early Childhood), 2023)
During the Covid-19 pandemic, various problems emerged, one of which was in the field of education, especially in the teaching and learning process. In this new normal era, there is a new policy, namely online and offline combined learning. For this reason, the right strategy is needed so that online and offline combined learning. For that we need the right strategy so that online and offline combined learning in early childhood can run effectively but still adhere comply with health protocols. This research is qualitative descriptive study with a case study approach that aims to describe a combination of online and offline learning strategies during the covid-19 pandemic. The technique of collecting data was through interviews, observations and documentation. The subjects in this study were school principals, teachers, and group B children in SAIMS Kindergarten. Data analysis technique using Miles and Huberman nodes Data validation using triangulation of qualitative sources using descriptive methods. The result show that learning in SAIMS Kindergarten uses the blended learning method with strategy of equipping facilities and infrastructure by using greenscreen as a support for online learning and using a body temperature check tool and a sensor sink to improve health protocols when offline, systematically arranged learning tools,media and material. All teaching materials that have been prepared by educators before the new school year,use web schoology which specially designed to facilitate learning and there is a division of session time for children who cannot take lessons according to the schedule. Keywords: early childhood, combined online and offline learning, during the covid-19 pandemic